Cockayne Syndrome B protein selectively interacts and resolves intermolecular DNA G-quadruplex structures. - Liano,D; Chowdhury,S; Di,Antonio M (Journal of the American Chemical Society, 2021)
Guanine-rich DNA can fold into secondary structures known as G-quadruplexes (G4s). G4s can form from a single DNA strand (intramolecular) or from multiple DNA strands (intermolecular), but studies on their biological functions have been often limited to intramolecular G4s, owing to the low probability of intermolecular G4s to form within genomic DNA. Herein, we report the first example of an endogenous protein, Cockayne Syndrome B (CSB), that can bind selectively with picomolar affinity toward intermolecular G4s formed within rDNA while displaying negligible binding toward intramolecular structures. We observed that CSB can selectively resolve intermolecular over intramolecular G4s, demonstrating that its selectivity toward intermolecular structures is also reflected at the resolvase level. Immunostaining of G4s with the antibody BG4 in CSB-impaired cells (CS1AN) revealed that G4-staining in the nucleolus of these cells can be abrogated by transfection of viable CSB, suggesting that intermolecular G4s can be formed within rDNA and act as binding substrate for CSB. Given that loss of function of CSB elicits premature aging phenotypes, our findings indicate that the interaction between CSB and intermolecular G4s in rDNA could be of relevance to maintain cellular homeostasis.